Effectiveness Effectiveness of Synchronous and Asynchronous Learning Methods on Student Learning Outcomes - Syukur, Muh. Syarif S Abd.; Haeruddin, Haeruddin (Media Eksakta, 2025)
This study aims to determine the effect of synchronous and asynchronous learning on student learning outcomes in computer application courses. The population in this study were students of the Indonesian Language and Literature Education study program at Tadulako University. Sampling was done by purposive sampling technique so that 2 classes were obtained that were normally distributed and homogeneous. This research uses a quantitative approach with a quasi-experimental method. Data analysis used one sample t test with the help of jamovi application. The results showed that synchronous and asynchronous learning can improve student learning outcomes in computer application courses with an average value of 84.9 in the experimental class and 83.6 in the control class. The prerequisite test results obtained p value (0.263) >0.05 in the normality test (Shapiro-Wilk) shows that the data distribution is normally distributed, and the p value (0.889) >0.05 in the homogeneity test (Levane’s) shows that the variance of the two data groups is homogeneous. The results of hypothesis testing using independent samples t-test obtained p (0.021) > α (0.05), so Ho is accepted, indicating that there is no significant difference in the average test scores between synchronous and asynchronous learning.